INTENSIFICATION OF MASS TRANSFER IN PACKED COLUMN APPARATUSES (British Journal of Global Ecology and Sustainable Development, 2025)
This article analyzes the mass transfer processes carried out in packed column apparatuses and methods for their intensification. Packed columns are widely used in the chemical industry for separation, purification, and processing of substances. These devices increase the efficiency of mass transfer by expanding the contact surface between the gas and liquid phases through nozzles located inside them. The article also covers the shape and material of fittings, optimization of working parameters, intensification mechanisms through additional technologies (ultrasound, pulsation, electromagnetic field) and new generation fittings.